Effects of dietary supplementation of vitamin E, Andrographis paniculata nees and Curcuma longa L. on growth, carcass and meat quality of goats - Karami, Morteza (2010)
An investigation in the first experiment was carried out to determine the effects of dietary supplementation of Andrographis paniculata, Curcumin longa and vitamin E on growth performance, carcass characteristics, meat quality, antioxidant activity and fatty acid profiles of Kacang crossbred male goats. Thirty-two male goats (13.0±0.29kg) were assigned to four dietary treatments of eight goats each. The diets were basal – control (CN), and basal supplemented with 400 mg/kg vitamin E (VE), 0.5 percent turmeric powder (TU) or 0.5 percent Andrographis paniculata powder (AP). Feeding was ad libitum as a total mixed ration for 16 weeks (including two weeks adaptation). After 14 weeks, the goats were slaughtered according to the Halal method and the carcass split two parts (right and left). The longissimus dorsi (LD), infraspinatus (IS) and biceps femoris (BF) muscles were taken. The muscles were vacuum- packaged and conditioned for 0, 7 and 14 days in a chiller at 4oC. The feed intake was lower (P<0.05) for the AP than TU treatment, while the feed efficiency was higher (P<0.05) in the AP than the CN treatment, as well as total meat in the carcass and the rib eye muscle area. The percentage of cooking loss in the AP treatment was lower than CN in the fresh IS muscle (P<0.05). The Warner–Bratzler shear force (WBSF) value was reduced by the dietary supplementation in fresh LD (P<0.05). The effects of post mortem aging periods on the WBSF values in BF and IS muscles of goats fed AP treatment were significant. The dietary antioxidant supplementation treatments had significant effects on the L* (lightness), a* (redness), b* (yellowness) values, Chroma and Hue angle (P<0.05) in the LD, IS and BF muscles at different post mortem periods. AP and TU supplemented diets significantly reduced the WBSF value in LD (0day) and AP effect on IS (7 and 14 days). The AP and TU treatment improved the tenderness of BF muscle in different post mortem aging periods. The dietary antioxidant supplementation had significant effects on 2-thiobarbituric acid reactive substance (TBARS) values at 7 days (LD and IS) and 14 days (LD, IS and BF). The unsaturated fatty acids (UFA) in BF and IS muscles were significantly higher (p<0.05) in goats fed the AP diet compared to the other diets. In the second experiment was conducted to examine the effect of varying levels of AP and TU on the growth performance, carcass characteristics and meat quality of goats. Each treatment received one of the five diets based on the diet formulation in the first experiment. The diets were basal – control (CN), and basal supplemented with 0.25% AP (AP0.25), 0.75% AP (AP0.075), 0.25% TU (TU0.25) and 0.75% TU (TU0.75). Goat slaughtering and muscle sampling procedures were as in the first experiment. The final weight, average daily weight gain, feed to gain ratio, gain to dry matter intake percent, hot and cold carcass weight, dressing out percentage, were not significantly (P>0.05) affected by different levels of AP and TU supplemented diets. The goats fed the AP 0.75% supplemented diet had a higher feed efficiency than the goats fed the basal diet (P>0.05), apparently due to a decreased feed intake. The AP0.75 treatment produced a more desirable leaner carcass with a higher proportion of meat and lower weight of subcutaneous fat and a bigger rib eye muscle area than the CN treatment (P<0.05) which is related to the lower back fat adipose and internal body fat (P<0.05). The AP and TU levels significantly affected the L*, b*, chroma value and Hue angle at different post mortem aging periods in the LD, IS and BF muscles (P<0.05). Different dietary levels of AP and TU significantly (P<0.05) improved tenderness of the muscles and post mortem aging periods significantly (P<0.05) reduce the WBSF value of chevon. Results of a sensory panel evaluation showed that AP and TU levels significantly (P<0.05) affected the aroma, tenderness, juiciness and overall acceptability of the chevon. All the experimental diets reduced the TBARS value in all the three muscles. The different levels of AP and TU also reduced (P<0.01) the TBARS value in the blood plasma of goats. It can be concluded that supplementing basal diets with herbs and spices containing antioxidants resulted in a general improvement of meat quality and retardation of lipid oxidation compared to the control diet. Some polyunsaturated fatty acids (PUFA) especially PUFA n-3, in BS, IS and LD and also in blood plasma, tended to increase with increasing AP supplementation